Understanding inputs into innovation: Do cities substitute for internal firm resources? - Chris Forman; Avi Goldfarb; Shane M Greenstein (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2006)
We examine whether there is a tradeoff between employing internal (firm) resources and purchased external (local) resources in process innovation. We draw on a rich data set of Internet investments by 86,879 U.S. establishments to examine decisions to invest in advanced Internet technology. We find evidence of localization of substitution. In particular, we show that the marginal contribution of internal resources is greater outside of a major urban area than inside one. Agglomeration is therefore less important for highly capable firms. When firms invest in innovative processes they act as if resources available in cities are partial substitutes for both establishment-level and firm-level internal resources.
Keywords: R30; O33; L86; 330